Prognostic and Clinicopathological Value of Human Leukocyte Antigen G in Gastrointestinal Cancers: A Meta-Analysis - Peng, Yongjia; Xiao, Jian; Li, Wenyun; Li, Shuna; Xie, Binbin; He, Jiang; Liu, Chaoqun (Frontiers in Oncology, 2021)
Background: The prognostic value of human leukocyte antigen G (HLA-G) expression in gastrointestinal (GI) cancers remains controversial. Thus, this meta-analysis aimed to summarize available evidence from case-control or cohort studies that evaluated this association. Methods: The PubMed, EMBASE, Cochrane Library, and Web of Science databases were searched to identify relevant studies written in English published up to April 1, 2021, and with no initial date. Furthermore, the Google Scholar and Google databases were also searched manually for gray literature. The protocol for this meta-analysis was registered at PROSPERO (CRD42020213411). Pooled hazard ratios (HRs) or odds ratios (ORs) and 95% confidence intervals (CIs) were estimated for endpoints using fixed- and random-effects statistical models to account for heterogeneity. Publication bias was evaluated using a funnel plot, Begg’s and Egger’s tests, and the “trim and fill” method. Results: A total of 30 eligible articles with 5737 unique patients, including 12 studies on colorectal cancer (CRC), 6 on gastric cancer (GC), 5 on esophageal cancer (ESCC), 5 on hepatocellular carcinoma (HCC), and 2 on pancreatic adenocarcinoma (PC), were retrieved. Both univariate (HR = 2.01, 95% CI: 1.48 ~ 2.72) and multivariate (HR = 2.69, 95% CI: 2.03 ~ 3.55) analyses revealed that HLA-G expression was significantly correlated with poor overall survival (OS), regardless of the cancer type or antibody used. Subgroup analysis stratified by antibody showed that the 4H84 (I2 = 45.8%, P = 0.101) antibodies could be trustworthy and reliable for detecting HLA-G expression in GI cancers. Besides, HLA-G expression was found to be correlated with adverse clinicopathological parameters such as clinical stage, nodal status, metastasis, and histological grade but not tumor status. Conclusion: Elevated HLA-G expression indicates a poor prognosis for GI cancer patients, and screening for this marker could allow for the early diagnosis and treatment of GI cancers to improve survival rates.